Does The Education Influence Self Efficacy in Tuberculosis Patients? : Systematic Review - Fauziah, Ardianti; Zahroh, Chilyatiz; Nadatien, Ima; Hidaayah, Nur (Chakra Brahmanda Lentera Institute, 2024)
Background: Tuberculosis is still a health problem in the world, one of which is in Indonesia, which is ranked third after India and China. Tuberculosis is transmitted through the air and is caused by the bacteria Mycobacterium tuberculosis. This research aims to determine the effect of health education on self-efficacy in pulmonary tuberculosis patients. Methods: The method used in this research is a systematic review with a systematic review (PRISMA) using several journal databases from Google Scholar, Science Direct, and Pubmed from 2019-2024 with the keywords